Employing the Precautionary Principle to Evaluate the Use of E-Cigarettes - Bush, Ashley M.; Holsinger, James W.; Prybil, Lawrence D. (Frontiers in Public Health, 2016)
Electronic cigarettes (e-cigarettes) have emerged onto the public market as an alternative to tobacco cigarettes; however, science is inconclusive as e-cigarettes have not been thoroughly investigated, including their short- and long-term risks and benefits (1, 2). The question arises of whether e-cigarettes will become the future tobacco crisis. This paper connects the precautionary principle to the use of e-cigarettes in an effort to guide decision-makers in the prevention of adverse health outcomes and societal costs.